Digital Transformation Of Branch Offices: Balancing Physical and Digital Services In The Era Of Smart Banking - Juliana Putri (CV Putra Publisher, 2026)
The rapid development of digital technology has encouraged the banking industry to transform branch office services into a more integrated system that combines physical and digital services. Banking digitalisation through mobile banking, internet banking, artificial intelligence, and digital savings services has changed customer transaction patterns in the smart banking era. This study aims to analyse branch office transformation strategies in balancing physical and digital services while maintaining service quality and customer trust. This study employs a qualitative descriptive method based on a literature review of selected scientific journal articles, books, and relevant academic sources discussing digital banking transformation, service quality, customer trust, and smart banking. The literature sources were selected based on their relevance to the research topic, publication credibility, and contribution to the discussion of physical and digital service integration in banking. The results indicate that branch transformation does not entirely eliminate the role of physical services, but rather transforms branches into centres for consultation, education, and customer relationship management. Meanwhile, digital services serve to enhance transaction efficiency, speed, and flexibility. The challenges encountered include cybersecurity risks, low digital literacy, regulatory adaptation, and the need to enhance human resource competencies. Consequently, collaboration between technological innovation and service quality strategies becomes a crucial factor in supporting sustainable smart banking transformation.